Validation and Implementation of 3-Dimensional Scientific Literacy Test (Lisa3D Test): Measuring Scientific Literacy for Senior High School Students based on Scientific Reasoning, Scientific Inquiry, and Nature of Science - Susongko, Purwo; Abdul Wahab, Norwaliza Binti; Arfiani, Yuni; Kusuma, Mobinta (Universitas Negeri Semarang, 2024)
This research aims to validate and implement an instrument to measure the scientific literacy of high school science program students, including the abilities of Scientific Reasoning, Scientific Inquiry, and Nature of Science (NOS), called the Lisa3D Test. These three instruments were validated using the Rasch model approach and presented as a digital application. This research method was a descriptive survey with a quantitative approach. The research started from the test design, validation, and implementation stages. The types of validity used included content, psychometric, construct, and external validity. For construct validity, the instrument was tested on 197 high school students, while the implementation stage involved 407 students. The research results show that the Lisa3D Test has fulfilled all aspects of validity. The Lisa3D test has been successfully implemented via the page www.lisatest.id with a cut of 56% for the Scientific Reasoning test, 50% for the Scientific Inquiry test, and 56.25% for the NOS test. This research produces a standard instrument to measure the scientific literacy of high school science program students based on three dimensions, namely Scientific Reasoning, Scientific Inquiry, and Nature of Science (NOS). The Lisa3D test can be implemented on a broader scale and can be an additional criterion for graduating high school students so that all graduates can master science comprehensively.